IMPLEMENTASI ARTIFICIAL INTELLIGENCE DALAM APLIKASI CHATBOT SEBAGAI HELPDESK OBJEK WISATA PANTAI DI-BATAM DENGAN METODE FORWARD CHAINING - Situmorang, Jonatan; Koko Handoko (Computer Science and Industrial Engineering, 2024)
The chatbot application for recommending beach destinations in Batam City utilizes artificial intelligence and the forward chaining method on IBM Cloud's Watson Assistant. In the era of advancing technology, many individuals prefer seeking information through Google. Therefore, researchers have designed a website interface and chatbot to provide information assistance. The website features main menus such as home, tourism, gallery, contact, and chatbot, facilitating users in finding information about beaches in Batam. The forward chaining method, a type of inference engine, is employed to trace rules and offer solutions based on information gathering. The research outcomes encompass the website interface and chatbot displays, subjected to testing to ensure alignment with requirements. Usecase diagrams are employed in designing interactions between users and the system. Using Watson Assistant on IBM Cloud, the chatbot provides beach recommendations with greetings and questions upon the initial display. Accessing information through this website simplifies things for the community, eliminating the need to search for information from other sources. Through the forward chaining method, chatbot responses are determined based on pre-established rules. The objective of this application is to provide an efficient and user-friendly information search experience for Batam City users.